Foraging behaviour of the bee Osmia apicata Smith, 1853 (Hymenoptera: Megachilidae) - Gogala, Andrej (Acta entomologica slovenica (Ljubljana), 2011)
With observations and photography, the collecting of Onosma (Boraginaceae) pollen and nectar by Osmia apicata Smith, 1853 bees was studied. Pollen is collected by shaking the anther cone using the legs, an alternative method to the buzzing in this oligolectic bee species.
Keywords: Boraginaceae; čebele; Hymenoptera; Megachilidae; Onosma; opraševanje; Osmia; Osmia apicata